ANALISIS PERIZINAN PERKEBUNAN KELAPA SAWIT PT. EQUALINDO MAKMUR ALAM SEJAHTERA - Verri Setiawan (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTION During this Covid-19 pandemic, the Oil palm plantations are one of the mainstays of a superior community in order to support the development of the Indonesian national economy by opening up wide-open job opportunities. Indonesia has various wealth products that can improve the welfare of the people in order to increase regional income. In line with Law Number 32 of 2009 concerning Environmental Protection and Management, it is explained that “every business and or activity that has an important impact on the environment must have an Amdal. the formulation of the problem in this study How to analyze the environmental impact on oil palm plantations of PT. Equalindo Makmur Alam Sejahtera and what are the legal consequences for the environmental impact of PT. Equalindo Makmur Alam Sejahtera.This type of research is a type of empirical legal research, empirical legal research is oriented to primary data (research results in the field). The qualitative approach is carried out by conducting direct research in the field, namely by describing the special treatment of the Environmental Impact Analysis of oil palm plantations at PT. Equalindo Makmur Alam Sejahtera, as well as conducting interviews with several respondents who were deemed able to provide information.The result of this research and discussion is that PT. Equalindo Makmur Alam Sejahtera has conducted socialization regarding the company's AMDAL. In the event that it is not certain whether PT. Equalindo Makmur Alam Sejahtera has or not an AMDAL or Environmental Permit related to the oil palm plantation business being carried out. And the result of the environmental impact is the company's administrative sanctions in the form of termination of business licenses. Keywords: Environmental Impact Analysis, Legal Consequences, Oil Palm Plantation